Effect of lateral stiffness of secondary suspensions on heavy-haul locomotives stability during braking based on simulation and experiment - Guo, Lirong; Wang, Kaiyun; Chen, Zaigang; Shi, Zhiyong; Lv, Kaikai; Zhang, Rui (Transport, 2019)
This paper aimed to investigate the effect of the lateral stiffness of secondary suspensions on the stability capacity and running safety of heavy-haul locomotives during braking based on the dynamic model and the field braking tests. The dynamic model of heavy-haul locomotives included two double-unit locomotives and five coupler systems. Simulation results indicate that the increasing of the lateral stiffness of secondary suspensions can improve the stability capacity and running safety of heavy-haul locomotives. Then, the field braking experiments were conducted to validate the dynamic model. Comparing the experiment results of different locomotives, the coupler and carbody yaw angles are respectively decreased by 31.8 and 29.5%, which is consistent with the simulation results. It is worthy to be noted that lateral vibration behaviour of the carbody increases with the increasing of the lateral stiffness of secondary suspensions. For the improved locomotive, the main frequency of lateral acceleration is 1…2 Hz. However, the main frequency of lateral acceleration is 0.5…1 Hz in the original locomotive tests. Moreover, the high-frequency vibration is increased, especially in 10…12.5 Hz. According to the simulation and experiment results, the reasonable lateral stiffness of secondary suspensions is 400 kN/m for the test locomotive.